How to promote STEM competencies through design - Nichols, Kim; Musofer, Reshma; Haynes, Michele (Frontiers in Education, 2022)
Introduction This study explored the impact of a community of inquiry on Science, Design and Technology and Mathematics curriculum competencies of 159 Year six students as they carried out a design task. Methods A quasi-experimental design was employed with both qualitative and quantitative analyses. A community of inquiry approach was adopted by the teachers (n = 3) in the experimental group but not by teachers (n = 4) in the comparison group. Both groups participated in a learning sequence on electricity culminating in a design challenge in small collaborative groups. Results The results showed that the experimental group (n = 65) demonstrated significantly greater instances and a broader range of Science, Design and Technology and Mathematics competencies across the design task as well as significantly higher learning gains than their comparison group (n = 94) peers. Discussion The cognitive shifts towards higher competency development in the experimental group is stronger as a result of the reflection and reasoning required to engage in a community of inquiry.